The effect of educational intervention based on the self-efficacy theory of high school students in adopting preventive behaviors of COVID-19 - Zahra Rezaie; Vahid Kohpeima Jahromi; Vahid Rahmanian; Nader Sharifi (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: The COVID-19 pandemic has become a major problem for education systems. This study was conducted to investigate the effect of educational intervention based on the self-efficacy theory of high-school students in adopting preventive behaviors of COVID-19. MATERIAL AND METHODS: This quasi-experimental study was performed on Hazrat Zahra and Shahed high-school students in Jahrom (southern Iran) in 2021. In total, 160 students (80 each in the intervention group and the control group) were selected by multistage random sampling. Data collection tools included a demographic information questionnaire and self-efficacy in adopting preventive behaviors from COVID-19 researcher-made questionnaire. Questionnaires were completed by all participants before and 3 months after the educational intervention. The educational intervention was performed for 6 weeks by using an educational program based on Bandura self-efficacy theory. The intervention was performed during 12 sessions of face-to-face training in the classroom (two 1-h sessions per week), distributing educational packages and sending educational videos through cyberspace. Data were analyzed using Chi-square test, independent t test, paired t test, and linear regression. RESULTS: After the educational intervention, a significant difference was observed in the intervention group before and after the educational intervention (P = 0.018) and between the intervention and the control groups (P = 0.001) in the self-efficacy in adopting preventive behaviors from COVID-19 score. Also, the average self-efficacy score of students increased with an increase in parental education level and a history of COVID-19 in family members. CONCLUSION: Educational intervention based on self-efficacy theory was shown as an effective method to improve students' self-efficacy in adopting preventive behaviors from COVID-19.